The Dream of a Journey to the East: Mystery, Ritual and Education in Hermann Hesse’s Penultimate Novel - Roberts, Peter (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2008)
The Journey to the East is Hermann Hesse’s most deeply personal book. This enigmatic novel, with its deceptively simple narrative structure, lends itself well to multiple interpretations. To date, however, little attention has been paid by educationists to the book. This paper attempts to address this lacuna in the literature, beginning with an examination of the autobiographical and dream-like qualities of the novel. This is followed by a detailed analysis of the ritual of confession undertaken by H.H., the narrator and central figure in the book. H.H. lives in despair following the apparent dissolution of the League of Journeyers to the East. He seeks to overcome his despair, and learns the League is alive and well, through the character of Leo. At the end of the book H.H., having confessed his ‘sins’ and faced both his League brothers and himself, believes he has found the answer to his troubles. This paper argues that in his solution, H.H. fails to grasp of the importance of education, questioning and critique in self understanding and development. This being so, it is suggested, he will be unable to make the most of the knowledge available to him through the League archives, and his reflections on himself, Leo and the purpose of his existence will have only limited lucidity. He will, the paper concludes, have a long way to go on his journey to ‘the East’.